Operating system design : the Xinu approach - Comer, Douglas (Boca Raton : CRC Press, 2015)
The book guides readers through the construction of a conventional process-based operating system using practical, straightforward primitives. It gives the implementation details of one set of primitives, usually the most popular set. Once readers understand how primitives can be implemented on conventional hardware, they can then easily implement alternative versions. The text begins with a bare machine and proceeds step-by-step through the design and implementation of Xinu, which is a small, elegant operating system that supports dynamic process creation, dynamic memory allocation, network communication, local and remote file systems, a shell, and device-independent I/O functions.
Includes index.
Keywords: Xinu; Operating systems (Computers); System design